2012
DOI: 10.1002/adfm.201201900
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Dichroic Plasmon Resonance Modes of Gold Nanoparticles in Optical Thin Films

Abstract: A simple method is presented to tune the gold surface plasmon resonance (SPR) modes by growing anisotropic nanoparticles into transparent SiO2 thin films prepared by glancing angle deposition. In this type of composite film, the anisotropy of the gold nanoparticles, proved by gracing incidence small angle X‐ray scattering, is determined by the tilted nanocolumnar structure of the SiO2 host and yields a strong film dichroism evidenced by a change from an intense colored to a nearly transparent aspect depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 31 publications
4
70
0
Order By: Relevance
“…This bundling association has since been reported in a large variety of OAD thin films prepared by either evaporation or MS [143][144][145][223][224][225][226], and though development of this microstructural arrangement has been mainly reported for metal thin films [10,11,54,56,144,145,223,224], it has also been utilized as a template structure with oxides to develop new composite thin films (see for example [225] and [226]). Surprisingly, aside from some detailed discussions in early reviews [10], this bundling phenomenon has not attracted much attention in recent investigations on OAD thin films.…”
Section: Correlation Distance and Bundling Associationmentioning
confidence: 94%
See 1 more Smart Citation
“…This bundling association has since been reported in a large variety of OAD thin films prepared by either evaporation or MS [143][144][145][223][224][225][226], and though development of this microstructural arrangement has been mainly reported for metal thin films [10,11,54,56,144,145,223,224], it has also been utilized as a template structure with oxides to develop new composite thin films (see for example [225] and [226]). Surprisingly, aside from some detailed discussions in early reviews [10], this bundling phenomenon has not attracted much attention in recent investigations on OAD thin films.…”
Section: Correlation Distance and Bundling Associationmentioning
confidence: 94%
“…Recently, a host-guest strategy based on the formation of anisotropic Au nanodiscs inside the intercolumnar space of bundled OAD SiO 2 nanocolumns has been reported by our group [226]. The method relies on that the size, shape and orientation of gold nanoparticles are defined by the tilt angle of the nanocolumns and the intercolumnar space distance, which are experimentally determined by the zenithal angle of evaporation.…”
Section: Dichroism and Plasmonic Applicationsmentioning
confidence: 98%
“…In previous works we have shown that anisotropic gold or silver nanostructures presenting a dichroic plasmon resonance behavior can be prepared by different chemical or physical methods making use of a template effect of the bundles developed in OAD SiO 2 thin films. 47,48 In the present work, contrary to the electrochemical deposition of isotropic and spherical gold nanoparticles found on conventional ITO films, 49,50 a surface template effect of the plasma assisted OAD-ITO layers has prompted the electrochemical deposition of anisotropic gold nanostructures with a clear dichroic behavior of their surface plasmon resonance absorption.…”
mentioning
confidence: 84%
“…As explained in the experimental section other evaporation angles were not possible because of experimental restrictions. An outstanding characteristic of the microstructure of these plasma assisted OAD thin films is that the nanocolumns are not isolated but associate in the form of bundles 14,43,47,48,58 that stretch along a direction perpendicular to the incoming flux of evaporated material. Bundling association of nanocolumns in OAD thin films is a common phenomenon previously reported for a large variety of materials.…”
Section: 12mentioning
confidence: 99%
“…In some materials like SiO2 the tilted nanocolumns tend to aggregate in the form of parallel nanochannels arranged perpendicular to the direction of the incoming flux. This process, known as bundling, 22 has been recently exploited for the fabrication of tunable dichroic optical structures [23][24][25] . As shown in the Supplementary Information S2, room temperature GLAD deposition of SiO2 on PDMS foils (hereafter called G-SiO2/PDMS) yields nanocolumnar thin films where the bundling of the nanocolumns enhances the film in-plane anisotropy 23,24 .…”
mentioning
confidence: 99%